The role of the father in the care of the newborn in an intensive care unit during the covid-19 pandemic: a perspective from the new masculinities - Díaz Jassim, Nina Julieth; Robles Díaz, Elena Patricia; Díaz-Pérez, Anderson (Acta Bioethica, 2022)
Goal. To analyze the role of the father in the care of the newborn hospitalized in a neonatal intensive care unit.Methodology. This is a qualitative approach study. The selection of open sampling, convenience saturation, interviewing 10parents where at the end 4 were analyzed where the interviews were conducted in the Neonatal Intensive Care Units (NICU).The data was analyzed using the Atlas Ti 8.0® program through categories and content analysis. Results. Parents need to face thestressful situation of having their child in an intensive care unit, train and learn about the baby’s health condition, constantlycarry out introjection and reflective self-analysis, delve into the spiritual component and also focus on the I work as financialmanager. Conclusion. The father’s skills in the care of the hospitalized newborn were identified, such as patience and passionto perform the role of father. It is evident that man has a fundamental role in the care of the newborn.